Efektivitas Konseling Kelompok Menggunakan Teknik Sosiodrama untuk Meningkatkan Kepercayaan Diri Siswa di SMP Negeri 18 Pontianak - Restini, Anjellina; Yuline, Yuline; Amallia Putri (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
The purpose of this study is to evaluate the impact of group counselling at SMP Negeri 18 Pontianak that use sociodrama techniques to boost students' self-confidence. The study methodology is quantitative-experimental, utilising a one-group pre-test and post-test design with a pre-experimental design. Six students with poor self-confidence were included in the study's sample, which was drawn from the 67 students in classes VIII C and D. These students' questionnaire findings were analysed. Purposive sampling, a Non-Probability sampling approach, was employed in the sampling process. Calculations revealed that, on average, students' levels of self-confidence were 57 before receiving therapy (Pre-test) and 97 after receiving treatment (Post-test). The Paired Sample T-Test was used for statistical testing, and the results showed that there was a significant difference in the level of student self-confidence before and after receiving group counselling using sociodrama techniques. The T count was -9.530 with a sig value of 2 (Tailed) 0.000 < 0.05, meaning Ha is accepted and Ho is rejected. Thus, it was determined that group counselling at SMP Negeri 18 Pontianak employing sociodrama approaches was successful in raising students' self-confidence.